Analisis Kuantitas Air Bersih Terhadap Operasional Hygiene Sanitasi Di RSUD Sumber Sari Bantul Metro Selatan Tahun 2026 - Zikril Hakim; Wibowo Ady Sapta; Nawan Prianto; Mei Ahyanti (STIKES Columbia Asia Medan, 2026)
Clean water availability is an essential component of hospital hygiene and sanitation operations, including hand hygiene, environmental cleaning, linen management, food sanitation, and infection prevention. RSUD Sumbersari Bantul Metro Selatan still relies on one bore well and has limited water storage without a permanent backup source. This study aimed to analyze the adequacy of clean water quantity and quality in supporting hygiene and sanitation operations at RSUD Sumbersari Bantul Metro Selatan in 2026. This study used a descriptive analytic design. Data were collected through observation, interviews, water discharge and consumption measurement, document review, and laboratory examination of clean water samples. The analysis compared water availability, water demand, unit-based distribution needs, and water quality with the standards of Ministry of Health Regulation Number 2 of 2023. The results showed that during January-March 2026, the hospital served 154 inpatients and 1,028 outpatients and had 151 staff members. The total clean water requirement was 715.44 m3/90 days, while the available water was only 414.00 m3/90 days, fulfilling 57.87% of the required amount. The average daily need was 7.95 m3/day, compared with the availability of 4.60 m3/day. High-risk service units, particularly inpatient care, emergency services, intensive care, CSSD, isolation, maternity care, laundry, and nutrition services, require priority water distribution. Laboratory testing found Escherichia coli and total coliform at 19 CFU/100 ml each, exceeding the required standard of 0 CFU/100 ml. In conclusion, the quantity and microbiological quality of clean water at RSUD Sumbersari Bantul have not adequately supported optimal hygiene and sanitation operations.